2011
DOI: 10.1302/0301-620x.93b7.26125
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical performance of locking plate fixation with intramedullary fibular strut graft augmentation in the treatment of unstable fractures of the proximal humerus

Abstract: We evaluated the biomechanical properties of two different methods of fixation for unstable fractures of the proximal humerus. Biomechanical testing of the two groups, locking plate alone (LP), and locking plate with a fibular strut graft (LPSG), was performed using seven pairs of human cadaveric humeri. Cyclical loads between 10 N and 80 N at 5 Hz were applied for 1,000,000 cycles. Immediately after cycling, an increasing axial load was applied at a rate of displacement of 5 mm/min. The displacement of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…The first clinical experience of this technique was reported in the literature by Gardner et al [11] and showed encouraging results; seven out of seven fractures healed completely without a loss of reduction or fixation stability. Later, Neviaser et al [23] reported low rates of reduction loss (2.6 %), screw cut-out (0 %), and osteonecrosis (2.6 %), as well as high clinical outcome scores in a series of 38 patients with displaced PHFs treated with locking plate fixation and an endosteal strut augment. Biomechanical testing showed that medial support with an intramedullary fibular graft and angular stable fixation increased the overall stiffness of the bone-implant construct and reduced migration of the humeral head fragment compared with the locking plate alone [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…The first clinical experience of this technique was reported in the literature by Gardner et al [11] and showed encouraging results; seven out of seven fractures healed completely without a loss of reduction or fixation stability. Later, Neviaser et al [23] reported low rates of reduction loss (2.6 %), screw cut-out (0 %), and osteonecrosis (2.6 %), as well as high clinical outcome scores in a series of 38 patients with displaced PHFs treated with locking plate fixation and an endosteal strut augment. Biomechanical testing showed that medial support with an intramedullary fibular graft and angular stable fixation increased the overall stiffness of the bone-implant construct and reduced migration of the humeral head fragment compared with the locking plate alone [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…19 Biomechanical testing showed that medial support with an intramedullary fibular graft and angular stable fixation increased the overall stiffness of the bone-implant construct and reduced migration of the humeral head fragment, as compared with the locking plate alone. [20][21][22][23] In cadaveric specimens, Chow et al showed how fibular allograft augmentation could increase the strength of the locking plate to withstand repetitive varus loading. None of the augmented constructs failed prior to 25,000 cycles, while 6 of the 8 nonaugmented constructs failed at an average of 6604 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, tests under increasing loads showed that the maximum failure loads and stiffness in the locking plate with intramedullary fibular grafts were significantly higher than those in the locking plate alone. 20 Osterhoff et al recently tested a similar construct in synthetic bone of a proximal humerus locking plate augmented with an intramedullary fibular allograft strut. Significantly lower intercyclic fragment motion, lower overall fragment motion and a lower residual gap-distance deformation after 400 cycles of loading was recorded for the group with the fibular graft when compared with the conventional technique.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Bae et al 24) reported that strut bone augmentation significantly increased the maximum failure load and stiffness of construct with locking plate fixation in proximal humerus fracture compared with the construct with locking plate fixation alone. Saltzman et al 27) reported in their systemic review that fibular strut allograft was a viable option in treating proximal humerus fractures, despite great heterogeneity in the literature regarding the use of fibular strut allografts as an adjunct to open reduction internal fixation of proximal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%